A note on radionuclide 137Cs and 40K concentrations in Dall’s porpoises, Phocoenoides dalli, in coastal waters of Japan - Kasamatsu, F.; Kawabe, K.; Inatomi, N.; Murayama, T. (J. Cetacean Res. Manage., 1999)
Concentrations of artificial radionuclide 137Cs and natural radionuclide 4°K in Dall’s porpoise, Phocoenoides dalli, from the Pacific coast of northern Japan in 1996 are presented. Concentrations of 137Cs in muscle tissue from two male Dall’s porpoises were 0.153 ± 0.01 l and 0.234 ± 0.016 Bq kg-1 wetweight, and those of4°K were 104.0 ± 0.3 and 107.8 ± 0.9 Bq kg-1 wet weight, respectively. Concentration factors (CF, concentration in animal/concentration in sea water) for the two porpoises are 59 and 90 for 137Cs, respectively. These concentrations and CF values are within published ranges for marine fish in coastal waters. The CFs obtained in this study suggest that the trophic position of Dall’s porpoises is similar to that of the large piscivorous fish in the marine community in coastal waters of Japan.